Gusto mo bang maging reporter? youth's awareness and perception of the job of television field reporters - Sta. Ana, Genelie De Guzman 1990-
"This study aims to explore selected fourth year high school students' awareness and perception of the job of television field reporters. This study also looked at the influence of a video documentary featuring the actual work done by television field reporters to the career choice of the participants. Guided by Muzafer Sherif's Social Judgment Theory and Stuart Hall's Encoding and Decoding Model of Communication, this study tried to understand how the youth perceive the job of television field reporters, and how exposure to a video documentary influences their perception of the job. Two separate focus group discussions (FGD) were conducted with public and private high school students. One group comprised of nine students while another comprised of eight students, randomly selected from different sections. Findings revealed that prior to viewing the video documentary, most of the participants had negative perceptions of the job of field reporters, tagging it as dangerous and difficult. They also have low interest in watching news programs. Their awareness of the job of television field reporters is also limited to their perception of the job of news anchors, despite the difference of said jobs. These perceptions served as their basis in deciding whether they would like to pursue the career of a television field reporter or not. Most of the participants were not interested in the career. After viewing the 25-minute documentary that presented the day-in-a-life of a field reporter, the participants showed more appreciation of the news. They were able to differentiate the news anchor from the field reporter. Additionally, they also showed appreciation of the tasks performed by the reporter. Seeing how a two to three-minute report is constructed, the participants expressed greater appreciation of the news content and the reporter who delivered it. However, pre-conceived notions about the difficulty of the job were reinforced through the video. Beacuse of this, the participants still do not wish to pursue the career of television field reporters. Additional factors that affected their career choices are parent's choice, projected financial rewards of more lucrative careers, and the student's skills. On a larger scale, this study is reflective of the youth's psyche: how they view the job of field reporters, how they appreciate and value news and news programs, and how, lesser and lesser youth consider embarking on the career of field reporting. Furthermore, this study also touched on the waning interest of the youth to news programs. This may be an interesting avenue to explore. Do we really have news programs that are specifically targeted to the youth audience? The researcher believes that before an adolescent develops appreciation for the field reporter, and of their job as a career, he/she must first be interested in the news."